Tiny beautiful things : advice on love and life from Dear Sugar - Strayed, Cheryl, 1968- (Vintage Books, 2012)
"Tiny Beautiful Things" brings the best of Cheryl Strayed's published and never-before-published online columns in one place and includes a new introduction by Steve Almond. Life can be hard, life can be great. For years, the anonymous author of Dear Sugar was the one to turn to for advice. Now, the best of Cheryl Strayed's online columns are collected in one place for you to enjoy-- and learn from.